The impact of tractor drawbar height on performance and optimization using response surface methodology - Ali Yavuz Şeflek; Nuri Orhan; Mete Özkan (Scientific Reports)
Abstract This study explores the impact of tractor drawbar height (520, 530 and 540 mm from the ground) on key performance indicators, including pulling force, fuel consumption, pulling power and overall tractor efficiency. Present experiments were conducted on a special pulling power test track under controlled conditions at the Directorate of Agricultural Equipment and Machinery Test Centre of the Ministry of Agriculture and Forestry. Data were collected at different tractor forward speeds and performance parameters were modeled and optimized using Response Surface Methodology (RSM), a statistical approach widely used for multi-factor optimization. Present findings revealed that a drawbar height of 520 mm yielded the highest pulling force (47.4 kN) at a speed of 5.48 km h−1, while the same height combined with a speed of 8.33 km h−1 produced the maximum pulling power (78.75 kW) and the lowest specific fuel consumption (267.03 g kWh−1). Statistical analysis confirmed that both drawbar height and tractor speed had significant effects on pulling force and fuel consumption (P < 0.05). However, for overall tractor efficiency, only tractor speed showed a significance. The developed RSM models demonstrated high predictive accuracy, with an R² value of 0.98 for pulling force and error metrics such as RMSE of 0.42% for efficiency, highlighting the reliability of the approach. The study concludes that optimizing the drawbar height and tractor speed not only improves pulling performance but also enhances fuel efficiency, offering a practical framework for achieving sustainable agricultural practices. Present findings emphasize the critical role of drawbar height adjustments in minimizing energy losses and maximizing operational efficiency during field operations.